2001
DOI: 10.1006/aphy.2000.6129
|View full text |Cite
|
Sign up to set email alerts
|

The Rest-Frame Darwin Potential from the Lienard–Wiechert Solution in the Radiation Gauge

Abstract: In the semiclassical approximation in which the electric charges of scalar particles are described by Grassmann variables (Q 2 i = 0, Q i Q j = 0), it is possible to re-express the Lienard-Wiechert potentials and electric fields in the radiation gauge as phase space functions, because the difference among retarded, advanced, and symmetric Green functions is of order Q 2 i . By working in the restframe instant form of dynamics, the elimination of the electromagnetic degrees of freedom by means of suitable secon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
184
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 69 publications
(185 citation statements)
references
References 98 publications
0
184
0
1
Order By: Relevance
“…[11] and then applied to the isolated system composed by N scalar charged particles plus the electromagnetic field [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] and then applied to the isolated system composed by N scalar charged particles plus the electromagnetic field [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a 12 In a way analoguous to the angular momentum composition in quantum mechanics; note that this spin clustering is independent of the center-of-mass clustering associated with the Jacobi coordinates: the existence of these two unrelated clusterings might prove to be a useful and flexible tool in molecular physics. dynamical definition of vibration, which replaces the S = 0 C-horizontal cross section of the static approach 13 , is based on the requirement that the components of the angular velocity vanish. Actually, the angular velocities with respect to the dynamical body frames become now measurable quantities, in agreement with the phenomenology of extended deformable bodies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [27,28] a fully relativistic formulation of classical atomic physics in the rest-frame instant form of dynamics was given with the electro-magnetic field in the radiation gauge and with the electric charges Q i of the positiveenergy particles being Grassmann-valued (Q 2 i = 0, Q i Q j = Q j Q i for i = j) to regularize the electro-magnetic self-energies on the world-lines of particles. In the language of QED this is both a ultraviolet regularization (no loop contributions) and an infrared one (no brehmstrahlung), so that only the onephoton exchange diagram contributes and its static and non-static effects are replaced by potentials in a formulation based on the Cauchy problem.…”
Section: Relativistic Atomic Physicsmentioning
confidence: 99%
“…[27] (the second paper is devoted to spinning particles) it is shown that the use of the Lienard-Wiechert solution (see the third paper in Ref. [27]) with "no incoming radiation field" allows one to arrive at a description of N charged particles dressed with a Coulomb cloud and mutually interacting through the Coulomb potential augmented with the full relativistic Darwin potential. This happens independently from the choice of the Green function (retarded, advanced, symmetric,..) due to the Grassmann regularization.…”
Section: Relativistic Atomic Physicsmentioning
confidence: 99%
See 1 more Smart Citation